U C Berkeley Co-op Friends Annual Heavy-Sacramento - Watkins, Howard::::::::: (1983)
Cathy Barkett, Joe Barkett, Janice Rau, Steven Rau, David Morse announcing Howard won Buffoon of the Party Award to applause, Bonnie Neary, Alan Pricco, Teresa Pricco (white dress), Janie Gumpert, Janice Rau, Steven Rau